Low Power Thermal Tuning in Resonant Vertical Junction Silicon Modulators Through Substrate Removal - Nicholas Jacob D. Martinez; Christopher T. Derose; Robert Jarecki; A. L. Starbuck; Andrew T. Pomerene; Douglas C. Trotter; Anthony L. Lentine (IEEE Photonics Journal)
We report on thermally tunable modulators, with efficiencies up to 2.16 nm/mW. Efficient performance was accomplished through integrated heater design and Si substrate removal, where the heavily N+ doped Si heater element is integrated into the body of the microdisk. For comparison, modulators with an external heater design were also tested with small diameter Si substrate removed. The external heavily doped N+Si heater bars were fabricated outside the diameter of the microdisk. Efficiency for external heater design was 0.68 nm/mW with substrate removed. Both types of thermal modulators were experimentally tested and simulated for a complete understanding of the Si substrate's influence on heat dissipation with both types benefiting significantly from substrate removal. Agreement between simulation and experimental results was greater than 80 $%$ in all instances.